EVALUATION OF WORK PERFORMED AT THE SERVICE AREA - Adilov , Okbuta; Yusupov , Azamat (SAMBHRAM XABARNOMASI, 2024)
This article provides the development of methodological recommendations and the application of their results in production in order to improve in time during the operation and ensuring road safety of road transport